Shorter Telomeres Related to Posttraumatic Stress Disorder Re-experiencing Symptoms in Sexually Assaulted Civilian Women - Carvalho, Carolina Muniz; Coimbra, Bruno Messina; Xavier, Gabriela; Bugiga, Amanda V. G.; Fonseca, Tamiris; Olff, Miranda; Polimanti, Renato; Mello, Andrea Feijó; Ota, Vanessa Kiyomi; Mello, Marcelo Feijó; Belangero, Sintia Iole (Frontiers in Psychiatry, 2022)
Telomeres are short tandem repeats of “TTAGGG” that protect the chromosome ends from deterioration or fusion of chromosomes. Their repeat length shortens with cell division acting as a biomarker of cellular aging. Traumatic stress events during adulthood or childhood have been associated with posttraumatic stress disorder (PTSD) and short leukocyte telomere length (LTL). The present study investigated whether LTL was associated with PTSD in a Brazilian sample of sexually assaulted civilian women. We assessed 64 women with PTSD following sexual assault (cases) and 60 women with no previous history of sexual trauma or mental disorders (healthy controls - HC). PTSD diagnosis and severity were assessed using DSM-5 (Diagnostic and Statistical Manual of Mental Disorders, fifth edition) and Clinician-Administered PTSD Scale for DSM-5 (CAPS-5), respectively. LTL was measured using multiplex real-time polymerase chain reaction (PCR). We observed that LTL was associated with re-experiencing symptoms (B = -0.16; Confidence Interval (CI) 95% = -0.027 – -0.005; Bonferroni-adjusted p-value = 0.02). We did not find an association between LTL and other PTSD symptom clusters or PTSD per se. In conclusion, our findings indicate that shorter LTL is associated with PTSD re-experiencing symptoms in recently sexually assaulted women.